PROTECTIVE EFFECTS OF TOTAL POLYSACCHARIDES IN COMPOUND KUQININ CANINE PARVOVIRUS INFECTION AND ITS INFLUENCE ON THE EXPRESSION OF BAX AND BCL-2 GENE BASED ON PATHOLOGICAL, ULTRASTRUCTURAL, AND APOPTOTIC CHANGES - L. Yi-Chen; Z. Zhao-Rong; L. Juan; G. Zhi-Sheng (Journal of Animal and Plant Sciences, 2019)
As one of the most dangerous infectious diseases to dogs, canine parvovirus (CPV) infection has been universally characterized by its short course, high incidence, strong infectivity, and high mortality rate. This study was conducted to observe the protective effects of total polysaccharides (TP) found in Compound Kuqin (CK) on parvovirus infected dogs, and the expression levels of Bax and Bcl-2 gene in small intestine were detected as main index. Compound Kuqin (CK) is composed of a variety of Chinese herbal medicine, including Radix Astragali, Radix Scutellariae, Flos Lonicerae, and so on. Fifty dogs were equally divided into five groups, including the CK, TP, positive, blank, and model groups. The blank group was injected intramuscularly with normal saline for 7 d, and the Astragalus polysaccharides were used as the positive control. For CK, and TP groups, all the experimental dogs were intramuscularly injected with CK solution, and TP solution (1.5 mL/Kg body weight) twice daily for 7 d, respectively, and challenged by CPV post-vaccination. For the model group, the dogs were challenged by CPV without treatment. Small intestinal tissues were collected from the experimental dogs, and were further studied by transmission electron microscopy. The apoptosis of small intestinal cells, and the expression levels of Bax and Bcl-2 genes and proteins were detected using TUNEL assay, real-time fluorescent quantitative PCR, and western blot, respectively. The results indicated that in the model group, the intestinal villi were desquamated, the epithelium cells were degenerated, and the rate of apoptosis was 11.45±1.70%, the expression levels of Bax, Bcl-2 mRNA and protein was 3.55, 0.45, 0.46, and 0.52, respectively, and the ratio of Bcl-2/Bax was 1.15. However, the intestinal villi of dogs in TP group were only slightly desquamated, the epithelium cells were also slightly degenerated, villi boundaries were clear, the rate of apoptosis decreased significantly (P≤0.01), the expression of Bax mRNA and protein decreased significantly (P≤0.01 or P≤0.05), and the expression of Bcl-2 and the ratio of Bcl-2/Bax increased significantly (P≤0.01).It showed that Total Polysaccharides in Compound Kuqin could protect the small intestinal tissue, and promote the recovery of the small intestinal tissue by inhibiting ultrastructural changes in the small intestinal lining in parvovirus infected dogs as well as reducing the cell susceptibility to apoptosis induced by Canine parvovirus.
Keywords: Polysaccharides in Compound Kuqin; Canine parvovirus; small intestinal tissue; Bax; and Bcl-2; protective effect